Idioms in the National News Rubric Category of Education on cnnindonesia.com - Heppy Atma Pratiwi (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2018)
Idioms are basically often used by speakers of language in communicating with the wider community. The use of idiom is intentionally done primarily to declare something indirectly to the other person. Many idiom words are often found both in print media, electronic media, and online media that has not understood its meaning. Society only review a little of the meaning he read without deepening the intent and content of the reading read. The idiom’s word is very difficult to understand cognitively because it requires a broad understanding in a sense of its own. This study aims to determine the form of idiom and meaning of idiom used in the national news section of the news column of the type and form of idiom in cnnindonesia.com. This research is descriptive which describes the description of object and result of study in narrative form. Based on the type of idiom, the use of a full idiom of 18 with a percentage of 40% while the idiom partially as much as 27 with a percentage of 60%. In this case, news writers are more likely to use a partial type of idiom.Keyword: idioms, news, education, online media